How should we assess knowledge translation in research organizations; designing a knowledge translation self-assessment tool for research institutes (SATORI) - Nedjat Sima; Nedjat Saharnaz; Majdzadeh Reza; Gholami Jaleh; Maleki Katayoun; Ashoorkhani Mahnaz; Yazdizadeh Bahareh (BMC, 2011)
Abstract Background The knowledge translation self-assessment tool for research institutes (SATORI) was designed to assess the status of knowledge translation in research institutes. The objective was, to identify the weaknesses and strengths of knowledge translation in research centres and faculties associated with Tehran University of Medical Sciences (TUMS). Methods The tool, consisting of 50 statements in four main domains, was used in 20 TUMS-affiliated research centres and departments after its reliability was established. It was completed in a group discussion by the members of the research council, researchers and research users' representatives from each centre and/or department. Results The mean score obtained in the four domains of 'The question of research', 'Knowledge production', 'Knowledge transfer' and 'Promoting the use of evidence' were 2.26, 2.92, 2 and 1.89 (out of 5) respectively. Nine out of 12 interventional priorities with the lowest quartile score were related to knowledge transfer resources and strategies, whereas eight of them were in the highest quartile and related to 'The question of research' and 'Knowledge production'. Conclusions The self-assessment tool identifies the gaps in capacity and infrastructure of knowledge translation support within research organizations. Assessment of research institutes using SATORI pointed out that strengthening knowledge translation through provision of financial support for knowledge translation activities, creating supportive and facilitating infrastructures, and facilitating interactions between researchers and target audiences to exchange questions and research findings are among the priorities of research centres and/or departments.